Health-Promoting Lifestyle Behaviors and Their Correlates Among Nursing Students in Saudi Arabia - Pacheco, Haidee Tablada; Sallam, Salwa Abd El Gawad; Dayrit, Richard Dennis Juinio; Villano, Dominga Narag; Briones, Marifa Libang; Al Morjan, Heba Kayied Deab (Nurse Media Journal of Nursing, 2025)
Background: A health-promoting lifestyle serves as the foundation for healthy living and is highly relevant to nursing students, who are expected to model such behaviors as future healthcare providers. However, few studies have examined these patterns among nursing students in regions such as Hail, Saudi Arabia.Purpose: This study aimed to evaluate the health-promoting lifestyle behaviors of nursing students and their correlations with demographic factors.Methods: A cross-sectional correlational design was employed. A total of 263 male and female participants provided demographic information and completed the Health Promoting Lifestyle Profile II (HPLP II) questionnaire through convenience sampling. Independent-samples t-tests were used to compare HPLP scores by gender, one-way analysis of variance (ANOVA) was used to compare scores across year levels, and Pearson’s correlation was applied to examine associations between HPLP scores and selected demographic variables, including year level, GPA, family income, and BMI.Results: The overall health-promoting lifestyle behavior was classified as good (M=142.88, SD=28.77). No significant differences were observed across gender or year level for any HPLP subdomains. GPA was positively correlated with health-promoting behaviors (r=0.34, p<0.001), whereas family monthly income was negatively correlated (r=–0.15, p=0.01). BMI and year level were not significantly associated with HPLP scores.Conclusion: Nursing students demonstrated generally good health-promoting behaviors. Higher academic performance was linked to more frequent engagement in such behaviors, whereas students from higher-income families displayed slightly lower engagement. These findings highlight the importance of culturally and contextually tailored interventions to support nursing students in adopting and maintaining healthy lifestyles.